Traumatic perforations of the rectum in the child - Vacarezza, Adolfo (Cirugía del Uruguay, 2020)
1) A review of 4 patients with a rare lesion in pediatric surgery is presented. 2) W e stablish and discuss the rules for a correct medical and surgical therapy. 3) The clinical evolution of the presented cases is discussed. 4) It is concluded, that rectal lesions are of extreme gravity and that an urgent medical and surgica1 therapy must be prometed.